How do people become foster carers in Portugal? The process of building the motivation - Diogo, Elisete (2021)
Act no. 142/2015 highlights the importance of children out-of-home being placed in a family context. However, foster care continues to be an almost absent component in the Portuguese childcare system. In 2017, it corresponded to just 3% of out-of-home care. This research aims to contribute to the understanding of the reasons for becoming a foster family. It adopted a qualitative approach, using carers' narrative interviews and practitioners semi-structured interviews, inspired by grounded theory. Foster family motivation is rooted in altruism, affection for children and sensitivity to maltreatment. These factors, as well as personal life course and contact with out-of-home care, induce a predisposition to become a foster family. The quality of the support services and the care professionals' performance also reveal key elements.